Mis-interpretasi Ayat Kepemimpinan Laki-Laki Atas Perempuan (Kritik Terhadap Tafsīr Feminis) - Lukman Hakim (Studia Quranika: Jurnal Studi Quran, 2017)
The feminist movement that advocates parity between male and female continues to spread until the point it even contaminates the interpration of the Qur’an. They judge the classical methods of interpretation as advocating the suppression of women. Thus, the classical interpretation methods must be frequently updated and must be changed in accordance with what’s relevant to today’s muslim society, and the method that should be applied is heremeneutics. This method demands the mufasir to use relativism, because no interpretation is absolute. If this method that they use, means that they consider the Qur’an and the bible as being the same, thus, the interpretation method is unsuitable with mufasirs, that were close to the prophet, with the arrival of islam came, the liberation and elevation of the status and the role of women in society.